Complete State Trials of the Tudor Era - Taylor, James D. (New York : Algora Publishing, 2019)
This book presents the documentation of all known recorded capital trials within the Tudor dynasty, each encapsulating the drama and intrigue of real history as Tudor law evolved from following the monarch's will to following clearly-established law. While capital punishment was common, several individuals accused of treason skillfully and successfully defended themselves.
Robert HickfordJohn Story; John Leslie, Bishop of Ross; Commission on the Use of Torture; William Parry; Anthony Babington and others; Edward Abington and others; Mary, Queen of Scots; Sir Richard Knightley; Philip Howard; John Udall; Robert of Essex; Captain Thomas Lee; _GoBack
Print version record.
eBooks on EBSCOhost
Keywords: Trials (Political crimes and offenses) -- England -- History -- 16th century -- Sources; Great Britain -- History -- Tudors, 1485-1603 -- Sources; Great Britain -- History -- Tudors, 1485-1603.; Grande-Bretagne -- Histoire -- 1485-1603 (Tudors); Procès (Crimes et délits politiques) -- Angleterre -- Histoire -- 16e siècle -- Sources; Grande-Bretagne -- Histoire -- 1485-1603 (Tudors) -- Sources; Trials (Political crimes and offenses); England; Great Britain; 1485-1603; History; Sources